Hubungan Dosis Tepung Gembili (Dioscorea esculenta) Dengan Tingkat Ekspresi Enzim Ampk-α2 pada Model Tikus Diabetes Melitus - neni oktiyani; sunarti Sunarti; Prasetyastuti Prasetyastuti; Jujuk Anton Cahyono (Medical Laboratory Technology Journal, 2015)
Alternative methods of controlling glucose levels in patients with diabetes is by type of food, either by utilizing yam flour. At the flour contained inulin and resistant starch that can activate the enzyme AMPK-α2. Activation of these enzymes will stimulate glucose transport in skeletal muscle and liver, thus causing a decrease in glucose production. Varying doses of flour is expected to affect the expression of AMPK-α2. This study aims to dosage relationship yam flour (Dioscorea esculenta) with tigkat-α2 AMPK enzyme expression in the nucleus skeletal muscle and liver in mouse models of diabetes mellitus. The study was a quasi-experimental design with Post Test Only Group Design. Rats were divided into 5 (five) groups, healthy mice, the mice with type 2 diabetes, and type 2 groups of diabetic rats with dietary intake yam flour addition of 1.25 g (TG-1:25),), 2.5 g (TG -2.5), 5.0 g (TG-5.0). Yam flour is mixed into the rat diet feed with varying doses. The results showed no significant correlation between the dose of yam flour with AMPK-α2 expression levels in skeletal muscle nuclei (p = 0.312) and liver (p = 0.474) in a mouse model of DM. The need for other studies using other types of food as an alternative arrangement of food for patients with diabetes